El estado del mundo y el segundo periodo de George W. Bush - Valdés Ugalde, José Luis (Revista Mexicana de Política Exterior, 2022)
According to Valdés Ugalde, war has once again become a world pattern and part and parcel of the modern diplomatic setup, a state of affairs that contrasts with the recent search for change and consensus through democracy. It is in this context that the United States is situated, for its control of the international arena has been attained through power, the use of force and messianism. The author supports this theory from an historic viewpoint, basing himself on the official discourse of the United States in recent times, especially since September 11, 2001. He believes that the US democratic system is facing a crisis of local and global consensus unheard of since the Viet Nam War and the Watergate scandal. George W. Bush’s strategy during the 2004 electoral process, he says, was surrounded by revived conservatism and exacerbated nationalism, where Americanism was postulated as an ideology in and of itself. Valdés Ugalde also mentions the recent appointments of Condolezza Rice and Alberto R. Gonzales, which, far from favoring ethnic, group or binational interests, represent greater cohesion in the formulation of Bush’s foreign policy, given that their views largely coincide with the President’s ideological convictions. The author concludes by raising several questions concerning US policy toward Latin America, particularly Mexico.